Asymptomatic azygos vein overflow in a young patient with primary mediastinal seminoma. Issue 12 (30th September 2019) - Di Liello, Raimondo; Sparano, Francesca; Iacovino, Maria Lucia; Viscardi, Giuseppe; Della Corte, Carminia Maria; Ronchi, Andrea; Sabetta, Rosa Laura; Fasano, Morena; Vicidomini, Giovanni; Reginelli, Alfonso; Ciardiello, Fortunato; Morgillo, Floriana
Abstract : The azygos system is the most important pathway for decompression of the superior vena cava (SVC) when a blood flow obstruction to the right atrium is present. Thoracic and mediastinal malignancies, mainly lung cancers, are responsible for 60%–85% of superior vena cava syndrome (SVCS) cases. An uncommon origin of SVCS is primary malignant mediastinal germ cell tumor (PMMGCT) which represent 1%–4% of all mediastinal tumors and can be divided into two broad groups: seminomas and nonseminomatous germ cell tumors (NSGCTs). Primary mediastinal seminomas clinical presentation is often nonspecific, even if the majority of patients present with superior vena cava involvement. Here, we present the radiologic features of asymptomatic azygos system overflow in a patient with primary mediastinal seminoma.